Ethical Attitude of the Evangelical Christian Church in Halmahera towards the 2024 Political Year in North Halmahera - Remelia F. Dalensang; Marton Tasiringan (IHSA Institute, 2024)
This research uses a qualitative method with a descriptive analysis approach. The purpose of this research is to determine the ethical attitude of the Church to prevent the impact of differences in elections in political moments and to find out whether the church can be involved in practical politics or not. Based on the research results, the process of socialization to the congregation in order to provide a good understanding of politics has been conducted for a long time. However, there are some problems such as this socialization cannot be performed to all GMIH congregations in North Maluku. The other results of the research, as at the Evangelical Christian Church in Halmahera, show that the congregation is not involved in practical politics but the Church is present to provide understanding to all congregations about good politics and invite them to give their rights (votes), both to elect and be elected in the general elections (Pemilu) or in the regional elections (Pemilukada) in 2024